Studi Tentang Penerapan Fatwa Bunga Bank di Indonesia - Yuliatin Yuliatin (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
The goal of this writing is to discuss the application of the verdict of bank interest in indosia. Based on the Indonesian council of religious scholars, the bank interest is illegitimate. Unfortunately, most of muslim including NU and Muhammadiyah though that verdict was made and applied without well-consideration. The Indonesian council religious scholars, on the other hand, stated that the verdict is flexible, so the Indonesia my follow or not . there fore, this article discusses the verdict of Indonesian council of religious scholars from methodological and content aspect. From methodological aspecy, Indonesian council of religious scholars only consider the secondary sources, such as the scriptures and the muslim scholars agreement, and else. Based on the content, the Indonesian council of religious scholars considers conventional bank interest as illegitimate based on its account. Also, muslim has another alternative for bangking that is Islamic banks (sharia banks) wich give facilities to the people. If there is no islamic banks, the muslim my make accounts in conventional.